Public expenditures in the selected economic industries: Policy implications for the period of the COVID-19 pandemic crisis - Veronika Mitkova; Vladimír Mlynarovič (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
The paper presents the constrained multiplier methodology in semi-input-output analysis and quantifies the effect of the government support to the industries mostly affected by COVID-19 pandemic in Slovakia. In contrary to traditional input-output analysis, the methodology in this paper allows to drop assumptions of the unlimited industries' supply. The analysis is conducted for 57 economic industries, households, governments, and the foreign using the Global Trade Analysis Project data. The analysis not only identifythat the most stricken industry is the recreation and other services together with transport industry, it also enumerates the effects of the government subsidy. Each Euro of the government support to the Recreation sector increases the Gross Domestic Product by 1.21 Euro, to the Transport industry by 0.93 Euro, while to the automotive industry included to this analysis by 0.54 Euro. The government subsidy should aim the Recreation industry not only for the highest decline of sales during the pandemic, also for the highest number of firms at risk and because of very effective return of the government support which almost triples the total output and generates more than one Euro of the GDP.
Keywords: C67; 330; Public Expenditures; Covid-19; Semi-Input-Output Analysis; Multiplier